Arrow behaviour in the lateral plane during and immediately following the power stroke of a recurve archery bow - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2013)
An arrow exiting a recurve archery bow flexes laterally. This is important in ensuring that the rear of the arrow clears the bow without obstruction and is a consequence of the manner by which the string leaves the archer`s fingers. Pekalski and then Kooi and Sparenberg modelled the arrow behaviour during the bow`s power stroke using a flexible beam. In this article, the method used by Kooi and Sparenberg has been extended to remove subjective components, to include the carbon fibre composite arrows now used almost exclusively in competition and to consider the arrow after it has left the bow. The various user-selectable parameters have been examined to ascertain their impact on archer performance. The modelling was tested against measured parameters of a number of expert archers and against the use of the recurve bow in a shooting machine.